The establishment of the three-phase technique and tactic analysis model for the players with the playing style of chop-and-attack - Zhang, X. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
Research Objective: There are lots of indicators in table tennis technique and tactic. Starting point of analysis and diagnosis in technique and tactic should be according to the actual situation: time, space, status, power and etc... Evaluation of each rally contains the technology, lines, placement, effect elements, the cohesion between the rally and rally, and the time of the ball in the whole period. Based on the classic three phases technique and tactics indicator system, according to the characteristic of the players with the playing style of chop-and-attack, the paper had chosen the analysis indicators to meet the requirements for the real situation in technique and tactic step by step, and built an indicator database. Straighten out the relationship between the indicators, forming a reticular structure, then set up three phases technique and tactic analysis model of the players with the playing style of chop-and-attack. Research methods: Using Simi Scout technique and tactics video analysis software, combined with the classic three- phase technique and tactics analysis method. Research results (1) Five indicators, the first one was the number of the games, the second was three-phase, the third was per phase indicator, the fourth is the specific technology, and the fifth is score or not. (2) Sub indicators in serve and attack phase included serve (short, half-long, long), control after serve (cut, split or push), attack after serve (over the table, long shot), chop after serve (forehand, backhand) (3) Sub indicators in receive and attack phase included control in receive (cut, split and push), attack in receive (over the table, long shot), chop in receive (forehand, backhand), attack after receive (forehand, backhand), control or defence after receive (forehand, backhand), chop after receive (forehand, backhand). (4) Sub indicators in the phase of sustained rally included turn to attack (forehand, backhand and pivot), passivity (forehand, backhand and pivot) and chop (forehand, backhand and pivot). (5) This technology and tactics model has been successfully applied into the Chinese national table tennis team, and obtained a certain practical benefits. Key words: the playing style of chop-and-attack, three phase technique and tactic analysis method, model